The public health impact of recombinant herpes zoster vaccination in adults over 50 years in Spain - Andrea García; Laura Amanda Vallejo-Aparicio; Rosario Cambronero Martinez (Taylor & Francis Group, 2024)
The recombinant zoster vaccine (RZV) is included in the Spanish National Immunisation Programme for adults 65 years of age (years), with a potential progressive catch-up program for adults 66-80 years, starting with 80 years. However, the risk of herpes zoster (HZ) increases significantly from 50 years. We estimated the public health impact (PHI) of vaccinating adults ≥50 years in Spain versus no vaccination, using a Markov model adapted to the Spanish setting. The model simulated a hypothetical ≥50 years cohort over a lifetime, with inputs from Spanish publications, databases, or publications from other countries where Spanish data were unavailable. Base case inputs included 67.7% RZV coverage and 61.1% second dose compliance. Outputs included clinical outcomes avoided, healthcare resource use avoided, and number-needed-to-vaccinate (NNV) to prevent one HZ case. Deterministic (DSA) and probabilistic sensitivity analyses (PSA) were also conducted. The model estimated that, compared with no vaccination, vaccinating adults ≥50 years in Spain (N = 19,850,213) with RZV could prevent 1,533,353 HZ cases, 261,610 postherpetic neuralgia episodes, 274,159 other complications, and 138 deaths through the cohorts' remaining lifetime, mostly in the 50-59 years cohort. Furthermore, 3,500,492 primary care visits and 71,156 hospitalizations could be avoided, with NNV = 9 to prevent one HZ case. DSA predicted NNV = 7 to prevent one HZ case when second dose compliance was increased to 100%. PSA demonstrated ≥200,000 and ≥1,400,000 cases could be prevented in 86.9% and 18.4% of simulations, respectively. Starting RZV from 50 years could therefore prevent a substantial number of HZ cases and complications. Increasing RZV coverage and second dose compliance could further alleviate PHI of HZ.